(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nowadays, there are many challenges faced in the field of biomedicine to treat patients. Pharmaceutical applications of hydrogel play a very significant role in wound healing, drug delivery, and many more. Hydrogel has become an important tool for many such applications. Hydrogel technology has grabbed attention because of its unique properties and network structure, both physically and chemically. Hydrogels are available as natural or synthetic polymers. Hydrogel moldable properties are the most important characteristic due to which it can be easily modified and used in different applications. We are able to produce polysaccharides, polypeptides, and nucleic acids in hydrogels. Protein-based hydrogels consist of collagen, elastin, fibrin, gelatin, silk fibroin, and many others are mentioned in the research.